2021
DOI: 10.1177/14673584211013509
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between the length of stay and various determinants at one of the best European destinations

Abstract: Studies scrutinizing the tangible and intangible factors regarding the length of stay (LOS) in a destination are rare. The emotional factors have not always been integrated into this analysis. We have contributed to fill this gap in the literature considering the degree of happiness with the tourist destination. We used a sample of 1253 tourists and three regression models were estimated (OLS regression model, a Weibull survival model and a zero-truncated negative binomial) to study the LOS. We verified that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…We concluded that a good gastronomic experience contributed to the satisfaction of tourists, and consequently, to increase their levels of happiness. We also know that emotional factors related with happiness affect the length of stay (LOS) in a destination (Vieira et al, 2021), and consequently there will be a positive impact in economic terms. These types of factors must be included in the analysis of the attractiveness of a tourist destination in addition to other attributes, namely heritage richness, culture, climate, prices, among others.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…We concluded that a good gastronomic experience contributed to the satisfaction of tourists, and consequently, to increase their levels of happiness. We also know that emotional factors related with happiness affect the length of stay (LOS) in a destination (Vieira et al, 2021), and consequently there will be a positive impact in economic terms. These types of factors must be included in the analysis of the attractiveness of a tourist destination in addition to other attributes, namely heritage richness, culture, climate, prices, among others.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Others, such as Perez and Sampol (2000), Wang et al (2006), Apostolakis and Jaffry (2009), Marrocu et al (2015), and Serra et al (2015) use daily personal expenditure, thereby acknowledging that daily spending and length of stay are two different decisions, albeit interrelated. This, in turn, gives rise to the analysis of length of stay independently, such as the works of De Menezes et al (2008), Barros and Machado (2010), Thrane and Farstad (2012b), Montaño et al (2019), Vieira et al (2021), and Atsız et al (2022). Whether modeling daily spending or length of stay, literature repeatedly reports measures of tourists’ socioeconomic characteristics, trip-specific choices, and psychological attributes as valid exogenous determinants of both decisions, thereby lending collective support to reduced-form modeling of both decisions as one construct in the form of total expenditure, without disentangling potential asymmetries in the two processes.…”
Section: Literaturementioning
confidence: 99%
“…Length of stay, among the most scrutinized trip-specific determinants of expenditure, is frequently found to be endogenously determined by the same family of antecedents that determine spending Vieira et al, 2021;and Jackman and Naitram, 2023), leading to concerns over the consistency and unbiasedness of coefficients estimated without regard to the potential endogeneity of this important decision. Accordingly, literature has taken potential endogeneity of length of stay into consideration via IV regression as in Thrane (2015) or by means of structural equation modeling as in the case of Seiler et al (2003), Vetitnev (2015) and Štefko et al (2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sellers and Nicolau (2021) proposed a dependency model based on prospective theory, in which the two basic principles of this theory, aversion to loss and decreasing sensitivity, are introduced to study the effect of visitor satisfaction on a critical result and the expense of the visitors in the winery. Vieira et al (2021) studied the relationship between length of stay and the combination of tangible and intangible aspects of the tourist experience in the analysis of their influence on LOS. Cho et al (2017) identified underlying dimensions that represented limitations for visiting wine regions and segmented the wine tourism consumer into five mutually exclusive cluster segments.…”
Section: Introductionmentioning
confidence: 99%